2013
DOI: 10.1179/1607845412y.0000000067
|View full text |Cite
|
Sign up to set email alerts
|

Do SLCO1B3 (T334G) and CYP3A5*3 polymorphisms affect response in Egyptian chronic myeloid leukemia patients receiving imatinib therapy?

Abstract: CYP3A5*3 polymorphism was associated with imatinib efficacy while the SNP SLCO1B3 (T334G) was not associated with the response to imatinib treatment in Egyptian patients with CML in chronic phase. These results prompt us to explore the effect of CYP3A5*3 in CML patients taking imatinib in a larger scale study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
1
17
3
Order By: Relevance
“…However, some of the studies have identified the involvement of single nucleotide polymorphism (SNPs) in inter‐individual and inter‐population pharmacokinetic variability The data reported are not sufficiently conclusive to translate into individual drug‐dosage adjustment. It is noteworthy that only one of these studies was conducted in African patients and none was from Nigeria where the drug has also been introduced as the drug of first choice for CML. Therefore, in the present study we investigated the association of genetic polymorphism in the genes encoding for CYP3A5 , ABCG2 and ABCB1 with the steady‐state trough plasma concentrations and clinical outcomes of imatinib in Nigerians with CML.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…However, some of the studies have identified the involvement of single nucleotide polymorphism (SNPs) in inter‐individual and inter‐population pharmacokinetic variability The data reported are not sufficiently conclusive to translate into individual drug‐dosage adjustment. It is noteworthy that only one of these studies was conducted in African patients and none was from Nigeria where the drug has also been introduced as the drug of first choice for CML. Therefore, in the present study we investigated the association of genetic polymorphism in the genes encoding for CYP3A5 , ABCG2 and ABCB1 with the steady‐state trough plasma concentrations and clinical outcomes of imatinib in Nigerians with CML.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…In vitro mTORC2 kinase assays and immunoprecipitations were performed using anti-Rictor antibody. E, SMMC-7721 cell lines were serum-starved overnight and pretreated with or without H2O2 (100 mmol/L) for 30 minutes before HGF ( cancerres.aacrjournals.org Downloaded from major aspects, the potential relationship of CYP3A5 polymorphism and cancer risk or drug metabolism (9)(10)(11)(21)(22)(23)(24)(25)(26). Moreover, Tsunedomi R concluded that the expression of CYP3A5 was drastically decreased in conjunction with venous invasion and might serve as a marker of progression and molecular target for treatment of HCV-associated HCC (27).…”
Section: Cyp3a5-induced Intracellular Ros Enrichment Is Responsible Fmentioning
confidence: 99%
“…Preliminary evidence supporting this thesis comes from a study in which genetic variation in OATP1B3 was shown to be linked with altered concentrations of imatinib in circulating cells as well as with altered oral clearance of the drug (Nambu et al, 2011). However, this same variant was not associated with response to treatment (Bedewy and El-Maghraby, 2013), and there is no evidence that this transporter is connected with imatinib-induced adverse events that would be either directly associated with uptake in a target tissue or indirectly through an effect on systemic drug levels.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 89%